2023
DOI: 10.1371/journal.pone.0279845
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between income and mental health among 16- to 24-year-olds: Analysis of 10 waves (2009–2020) of Understanding Society to enable modelling of income interventions

Abstract: A substantial body of evidence suggests that young people, including those at the crucial transition points between 16 and 24, now face severe mental health challenges. In this article, we analyse data from 10 waves of a major UK longitudinal household cohort study, Understanding Society, to examine the relationship between income and anxiety and depression among 16- to 24-year-olds. Using random effects logistic regression (Model 1) allowing for whether the individual was depressed in the previous period as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…We have shown that within- and between-individual variations in net equivalised household income are associated with greater prevalence of clinical-threshold level symptoms of poor mental health through measures such as SF-12 [ 80 ]. We therefore developed a simplified measure of household income based on the Institute for Fiscal Studies’ [ 41 ] ‘Your household's income: Where do you fit in?’ tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that within- and between-individual variations in net equivalised household income are associated with greater prevalence of clinical-threshold level symptoms of poor mental health through measures such as SF-12 [ 80 ]. We therefore developed a simplified measure of household income based on the Institute for Fiscal Studies’ [ 41 ] ‘Your household's income: Where do you fit in?’ tool.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, supporting Pickett and Wilkinson’s findings [ 82 ], Adeline and Delattre [ 2 ] endorsed both the Absolute Income Hypothesis (a positive and concave effect of income on health) and the Income Inequality Hypothesis (that income inequalities affect all members of a society). Our previous work [ 80 ] analysed data from 10 waves of the Understanding Society UK Household Longitudinal Study and found that each step down in average household income quintile was associated with a higher probability of reporting clinically significant symptoms of anxiety and depression among 16- to 24-year-olds. It also found that increases in income over time were associated with a reduction in that probability.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the authors of this study have undertaken similar analysis (Parra-Mujica et al, 2023) of Understanding Society data covering 16- to 24-year-olds over 10 waves of that UK Household Longitudinal Survey. That study found a much more consistent monotonic association between household income and the SF-12 Mental Component Summary measure of mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are conditions affected by SES, but they also affect income (Wilson and Finch, 2020), compounding inequality. We have argued that data from longitudinal studies and some controlled trials of income interventions indicate that the primary driver is income to health (Parra-Mujica et al 2022). This is likely the case for a large number of other health conditions, but depression is critical given that it has long been suggested as the most costly disease to society (Lecrubier, 2001) and the leading cause of disability worldwide (Bernardi and Johns, 2021).…”
Section: Inequality Mental Health and Policy Preferencesmentioning
confidence: 99%
“…The pandemic has highlighted the enormous cost of health inequalities that track socioeconomic inequalities. Indeed, we have found that over one third of all 16- to 24-year-olds met clinical threshold levels of anxiety and depression on the SF-12 measure in 2019 before the pandemic (Parra-Mujica et al (2022)), with morbidity driven by subjective socioeconomic markers such as perception of status and financial distress. However, progressive policymakers currently face a challenge in countries with rising inequality of wealth: there appears to be a trend of lower-income voters rejecting traditional parties of the centre and centre-left and supporting the centre-right and right-wing parties (Polacko, 2022).…”
Section: Introductionmentioning
confidence: 99%